Novel transparent conducting oxides for application in solar cells - Arca, Elisabetta (Trinity College (Dublin, Ireland). School of Physics, 2012)
In the present thesis deposition and characterization of transparent conducting oxides (TCOs) have been explored. The coexistence of transparency and conductivity in a material is often regarded as an unusual property, since transparent materials are most likely to be insulating while conductive materials are generally quite absorbing. This remarkable property can be easily achieved in wide band gap semiconductors, for which a band gap higher than 3 eV ensures transparency to the visible light while conductivity can be induced by doping, either intrinsic or extrinsic. Among the TCOs, n-type doping has been so far the most successful. In2O3:Sn, SnO2:F and ZnO:Al are the most commonly used n-type TCOs in commercial devices.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.